PENINGKATAN KEDISIPLINAN ANAK DENGAN TEKNIK MODELLING KELOMPOK A1 RA AL HUDA SIMOJAYAN AMPELGADING DAMPIT-MALANG - Anisah, Anisah (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
PThe increasing discipline in early childhood through modeling techniques by paying attention to aspects of the teacher's role and school culture at RA Al Huda Simojayan is running optimally. The aim of the research is to describe improving discipline through modeling techniques for children. The research methodology used is PTK (Classroom Action Research) with cycle stages produced in six meetings through observation data collection techniques, cycle instrument assessment, and documentation. This increase in ability can be seen from the results of the evaluation percentage obtained from each cycle, including the pre-cycle discipline aspect, 47%. In cycle I, the disciplinary aspect was 68.7% at the third meeting. After carrying out Cycle II, children's discipline increased to 93.4% for the average percentage of 4 variables from achieving an average value of 3.7 from 4 variables and with the highest value being 4. Suggestions that can be given include instilling discipline in early childhood using modeling techniques, children's development is in the imitative phase, so we as educators must be good models for them. Furthermore, it is hoped that we can provide discipline learning to children without having to force or pressure them, and use several innovations so that children's discipline research does not feel boring and stressful.